2022
DOI: 10.3389/fped.2022.884329
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Perceptions About Sensory Interventions in the Neonatal Intensive Care Unit: An Exploratory Qualitative Study

Abstract: BackgroundMothers play an important role in providing positive sensory experiences to their infants during NICU hospitalization. However, little is known regarding maternal perceptions about sensory-based interventions in the NICU. Further, understanding maternal perceptions was an important part of the process during development of the Supporting and Enhancing NICU Sensory Experiences (SENSE) program.MethodsTwenty mothers of very preterm infants were interviewed after NICU discharge and asked open-ended quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Families who perceive the NICU as more stressful may have lower presence during their infants’ hospitalization (Head Zauche et al, 2020). Parents who have received the SENSE program have reported that the use of volunteers engaging in co-occupations with their infants did put them at ease when they were unable to attend frequently (Lisle et al, 2022); however, this did not seem to decrease their reports of stress. With relationships observed in this study between parents conducting most of the sensory-based interventions and decreased reports of parental stress, it remains unclear whether engagement in more co-occupations with the infants played a role in decreasing parental stress and anxiety in this group or if parents with more stress experienced more barriers to engaging in co-occupations with their infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Families who perceive the NICU as more stressful may have lower presence during their infants’ hospitalization (Head Zauche et al, 2020). Parents who have received the SENSE program have reported that the use of volunteers engaging in co-occupations with their infants did put them at ease when they were unable to attend frequently (Lisle et al, 2022); however, this did not seem to decrease their reports of stress. With relationships observed in this study between parents conducting most of the sensory-based interventions and decreased reports of parental stress, it remains unclear whether engagement in more co-occupations with the infants played a role in decreasing parental stress and anxiety in this group or if parents with more stress experienced more barriers to engaging in co-occupations with their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of surrogates/volunteers has been suggested, successfully implemented, and studied (Clubbs et al, 2019). The use of volunteers to read and or provide touch, when parents were not available to engage in the daily recommended positive sensory exposures with their infants, has been deemed acceptable by parents (Lisle et al, 2022; Pineda et al, 2020). Of all the infants enrolled in a previous pilot study and randomized control trial (RCT) on the SENSE program, 85% had the majority of their positive sensory experiences conducted by their parents, while the remainder engaged in most of the experiences with volunteers or health care professionals (Pineda, Roussin, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other stakeholders impacted by NICU interventions include parents; however, parents were not invited to participate in these focus groups, as the intent of this study was to gather perspectives from health care professionals. Separate interviews were conducted to gather parental input on the SENSE program (Lisle et al, 2022). Focus groups for health care professionals were specifically selected above individual interviews, as focus groups are particularly helpful in the early stages of research (Smithson, 2000), and participants can dynamically co-construct ideas during an interactive discussion.…”
Section: Methodsmentioning
confidence: 99%
“…The goal is to empower parents to engage in the described sensory activities with their infant(s). In addition to the initial integrative review [6], a rigorous process of protocol development for the SENSE program took place, which included expert input from a multidisciplinary group of 108 health care professionals that defined sensory interventions implemented across different NICUs, 3 multidisciplinary focus groups that provided a critical review of the guideline [12,13], and interviews with 20 mothers of preterm infants who gave input on feasibility of implementing the SENSE program in the NICU [14]. All of these results were integrated to develop the evidence-based SENSE program.…”
Section: Introductionmentioning
confidence: 99%